=(3k+4)6+7(k+6)

Simple and best practice solution for =(3k+4)6+7(k+6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for =(3k+4)6+7(k+6) equation:


Simplifying
0 = (3k + 4) * 6 + 7(k + 6)

Reorder the terms:
0 = (4 + 3k) * 6 + 7(k + 6)

Reorder the terms for easier multiplication:
0 = 6(4 + 3k) + 7(k + 6)
0 = (4 * 6 + 3k * 6) + 7(k + 6)
0 = (24 + 18k) + 7(k + 6)

Reorder the terms:
0 = 24 + 18k + 7(6 + k)
0 = 24 + 18k + (6 * 7 + k * 7)
0 = 24 + 18k + (42 + 7k)

Reorder the terms:
0 = 24 + 42 + 18k + 7k

Combine like terms: 24 + 42 = 66
0 = 66 + 18k + 7k

Combine like terms: 18k + 7k = 25k
0 = 66 + 25k

Solving
0 = 66 + 25k

Solving for variable 'k'.

Move all terms containing k to the left, all other terms to the right.

Add '-25k' to each side of the equation.
0 + -25k = 66 + 25k + -25k
Remove the zero:
-25k = 66 + 25k + -25k

Combine like terms: 25k + -25k = 0
-25k = 66 + 0
-25k = 66

Divide each side by '-25'.
k = -2.64

Simplifying
k = -2.64

See similar equations:

| -6t=-9t+3t | | -10r=180 | | -5y-9+9y=6y+17 | | 9x^2+30x+25x=0 | | 7p-10=-10+7p | | h(t)=-3t^2+36t | | 5e-3=17 | | 7+(x+4)=12 | | 3r+16=16-10r+13r | | 7(s-5)=421 | | 2n+3=3-7n | | 4-8+6b=4+6b | | 5x+104=10x-6 | | =5(9k+2)+8(3+4k) | | 4d-5(3d+10)=126 | | 0=12p+-48 | | -10-4v=-4v | | 0=-3t^2+36t-5 | | (-13)(-3)= | | 4x-x+2=3x-8 | | 0=-4w+4w | | 5x=32.50 | | -1-10q=-10q | | n+10+9n+3= | | -10-7m=10+3m | | 8x+48=-6x-8 | | 6.9x+5=5.9x | | -7g=-g-6g | | 3a^2-8a-16=0 | | 5x+3=9x-5 | | 3.5d=-7/8 | | =x+(4+3x)7 |

Equations solver categories